Conservative surgical management of ectopic pregnancy and its role in preservation of future fertility - Dutta, Indranil; Dutta, Dilip Kumar; Dutta, Rumpa Banerjee (Asian Journal of Medical Sciences, 2021)
Background: Maternal Mortality is one of the most important issues in our country. Ectopic Gestation is one of the few reasons which contribute to it. The first successful surgical management of a tubal ruptured ectopic pregnancy occurred in 1883. In those times mortality was approximately 60%. Since then lot of development in management of ectopic pregnancy has taken place which has resulted in reduction of related mortality. But still it remains as one of the important topics as now due to more infections (i.e PID) and resulting ectopic gestations and further operative salphingectomies, there is a reduced chance of patient to conceive naturally afterwards. Hence role of conservative surgeries comes to the front. Aims and Objectives: Role of Conservative Surgical Management of Ectopic pregnancy and its relation to future fertility. Materials and Methods: This Study was undertaken at GICE Clinic, Cure Hospital, Kalyani, West Bengal India from January, 2008 to January 2019. During this period 64 patients were diagnosed and operated for Ectopic pregnancy. Results: Forty (62.5%) cases were in between 20-30 years of age. Forty-four (68.7%) cases had no issue. Forty-eight (75.0%) cases were from low socio-economic group. Sixty patients (93.7%) had the history of amenorrhea. It was also observed that history of induced abortion was in 20 (31.2%) cases, PID in 12 (18.7%) cases, appendectomy – 6 (9.4%) cases and history of previous IUCD insertion - 4 (6.3%) were found to be common amongst ectopic gestation cases. Twenty-four (37.5%) cases underwent linear salpingostomy, 8 (12.5%) cases had segmental resection with end to end anastomosis whereas 16 (25.0%) cases had salpingectomy and 16 (25.0%) cases had salpingo-opherectomy with tubectomy [opposite tube] were advocated. In 4(6.3%) cases of linear salpingostomy and 4 (6.3%) cases of segmental resection, the cases had to be re-operated again for unstable haemodynamic condition within 24 hours and were subsequently advocated to salpingectomy. Conclusion: Linear Salpingostomy was found to be a better option for women who desire to become future mother, than that of segmental resection and salpingectomy on affected tube (although pregnancy was reported as opposite tube)